Using Songs to Boost Vocabulary Mastery in English Classrooms - milarizka; Dzul Rachman; Abdul Halim (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
This study investigates the effectiveness of English songs in enhancing vocabulary mastery among university-level EFL students and explores their perceptions of song-based learning. Employing a mixed-methods design, quantitative data were collected through pre-test and post-test vocabulary assessments, while qualitative data were obtained via semi-structured interviews. Participants were 23 English Education students at Muhammadiyah University of East Kalimantan selected through purposive sampling. Quantitative analysis using a paired-sample t-test revealed a statistically significant improvement in students’ vocabulary mastery after the intervention (p < .001), indicating a strong instructional effect. Beyond score improvement, the findings revealed that students demonstrated increased ability to infer word meanings from context and greater retention of newly learned vocabulary. Qualitative findings further supported the quantitative results, showing that English songs enhanced students’ motivation, engagement, and confidence in using new vocabulary, as well as improving their pronunciation awareness and listening comprehension. Nevertheless, students reported challenges related to fast song tempo and unfamiliar accents, which occasionally hindered comprehension. Overall, the findings suggest that English songs function not only as an effective tool for improving vocabulary mastery but also as a meaningful pedagogical medium that promotes contextual learning, learner engagement, and positive learning experiences in higher education EFL contexts.